The Entrepreneurship Education Improvement Efforts Through Teaching Factory Students of Vocational High School Negeri 2 Kendal - Purwidyantini, Setyo Herlina; Wisika Prajanti, Sucihatiningsih Dian; Widiyanto, Widiyanto (Journal of Economic Education, 2017)
To improve competitiveness of globalization is required to improve the quality of middle-educated human resources. Students of Vocational High School are equipped with entrepreneurship education to increase their knowledge and entrepreneurship skills through teaching factory. This study aims to (1) analyze the characteristics of teaching factory in Vocational High School, (2) to analyze teaching factory that has been run in Vocational High School Negeri 2 Kendal and entrepreneurship value who obtained by students, (3) formulate ideal teaching factory to improve entrepreneurship education of Vocational High School students in Kendal. This research uses qualitative method in the implementation of teaching factory program at Vocational High School Negeri 2 Kendal. The validity data done by triangulation with the source.The results showed that teaching factory in Vocational High School Negeri 2 Kendal, started from planning by teachers, production process until marketing of their products. The implementation of teaching factory can improve entrepreneurship education students of Vocational High School Negeri 2 Kendal. In the planning of students learning to oriented tasks and results. In the production process students learn to be responsible, disciplined, confident, dare to take risks, independence, cooperation. In facilitation students learn open to technology. In marketing students learn to be honest, passionate, hard work, confident, able to overcome difficulties / problems, able to see opportunities and like challenges. In the evaluation students learning to open receive input, criticism and advice from outside. The implementation of teaching factory at Vocational High School Negeri 2 Kendal, there is cooperation with government, parents, business world and industry, alumni, society and other education units. The financing of teaching factory activities comes from government grants. Additional capital got from the profit of sales products, which are divided by a certain percentage.Teaching factory ideal supported by the partnership, mentoring and financing. Partnership with government, parents, community, bussines and industrial company, alumni and other education units. Mentoring from teachers and bussines and industrial company, financing by government, parent and private sector